Study of reading habits 1986 - Gästrikland - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of five municipalities in Gästrikland: Gävle, Sandviken, Hofors, Ockelbo and Älvkarleby. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys, such as the opinion on how much it is reasonable to pay annually for a local morning paper subscription and the attitude to paying the subscription fee through automatic deduction from a bank account. The respondent also had to compare the two local papers Arbetarbladet and Gefle Dagblad with regard to a number of qualities. Furthermore the respondents had to indicate if their local morning paper ought to increase or decrease their efforts in a number of fields. Another question dealt with the importance of a number of values in life, such as having a pleasant life, freedom, happiness, self-respect etc.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of five municipalities in Gästrikland: Gävle, Sandviken, Hofors, Ockelbo and Älvkarleby. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys, such as the opinion on how much it is reasonable to pay annually for a local morning paper subscription and the attitude to paying the subscription fee through automatic deduction from a bank account. The respondent also had to compare the two local papers Arbetarbladet and Gefle Dagblad with regard to a number of qualities. Furthermore the respondents had to indicate if their local morning paper ought to increase or decrease their efforts in a number of fields. Another question dealt with the importance of a number of values in life, such as having a pleasant life, freedom, happiness, self-respect etc.
Läsvanestudien 1986 - Gästrikland
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap